MISTERI POLA ASUH SUPORTIF DAN KOMUNIKASI KELUARGA: RAHASIA KESEHATAN MENTAL ANAK YANG TERKUAK - Susanti Mulyanengsih; Shinta Pratiwi; Mulya Virgonita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Children's mental health is a crucial aspect of psychological development that is influenced by various family-related factors, particularly supportive parenting practices and the quality of family communication. This study aims to examine the effects of supportive parenting and family communication on the mental health of school-aged children in Bogor City. A quantitative approach with a correlational-predictive survey design was employed. The sample consisted of 312 children aged 8–12 years and their parents, selected using proportionate stratified random sampling from four districts in Bogor City. Data were collected using the Supportive Parenting Scale, the Family Communication Scale, and the Children's Mental Health Scale, all of which demonstrated satisfactory validity and reliability, with Cronbach's alpha coefficients of 0.891, 0.876, and 0.903, respectively. Data were analyzed using descriptive statistics, Pearson correlation, and multiple linear regression with the assistance of SPSS version 27. The findings revealed that supportive parenting had a positive and significant effect on children's mental health (β = 0.431; p < 0.001), as did family communication (β = 0.359; p < 0.001). Simultaneously, both variables explained 67.3% of the variance in children's mental health (R² = 0.673; F = 317.82; p < 0.001). These findings indicate that supportive parenting and effective family communication serve as important protective factors in promoting children's mental health. Therefore, strengthening parenting education programs and improving the quality of family communication should be prioritized as part of promotive and preventive efforts to enhance children's mental well-being in both school and community settings.